Neonatal Hypoxic–Ischemic Encephalopathy: Perspectives of Neuroprotective and Neuroregenerative Treatments - Pedroza-García, Karina A.; Calderón-Vallejo, Denisse; Quintanar, J. Luis (Neuropediatrics, 2022)
Hypoxic–ischemic encephalopathy (HIE) is a serious condition that could have deleterious neurological outcomes, such as cerebral palsy, neuromotor disability, developmental disability, epilepsy, and sensitive or cognitive problems, and increase the risk of death in severe cases. Once HIE occurs, molecular cascades are triggered favoring the oxidative stress, excitotoxicity, and inflammation damage that promote cell death via apoptosis or necrosis. Currently, the therapeutic hypothermia is the standard of care in HIE; however, it has a small window of action and only can be used in children of more than 36 gestational weeks; for this reason, it is very important to develop new therapies to prevent the progression of the hypoxic–ischemic injury or to develop neuroregenerative therapies in severe HIE cases. The objective of this revision is to describe the emerging treatments for HIE, either preventing cell death for oxidative stress, excitotoxicity, or exacerbated inflammation, as well as describing a new therapeutic approach for neuroregeneration, such as mesenchymal stem cells, brain-derived neurotrophic factor, and gonadotropin realizing hormone agonists.
Keywords: excitotoxicity; hypoxic–ischemic encephalopathy; inflammation; neuroprotection; neuroregeneration; oxidative stress